An interferon-γ-delivery system based on chitosan/poly(γ-glutamic acid) polyelectrolyte complexes modulates macrophage-derived stimulation of cancer cell invasion in vitro. (1st September 2015) - Cardoso, Ana P.; Gonçalves, Raquel M.; Antunes, Joana C.; Pinto, Marta L.; Pinto, Ana T.; Castro, Flávia; Monteiro, Cátia; Barbosa, Mário A.; Oliveira, Maria José
Graphical abstract: Abstract: Macrophages represent a large component of the tumour microenvironment and are described to establish interactions with cancer cells, playing crucial roles in several stages of cancer progression. The functional plasticity of macrophages upon stimulation from the environment makes them susceptible to the influence of cancer cells and also renders them as promising therapeutic targets. In this work, we describe a drug delivery system to modulate the phenotype of macrophages, converting them from the pro-tumour M2 phenotype to the anti-tumour M1 phenotype, based on the incorporation of a pro-inflammatory cytokine (interferon-γ) in chitosan (Ch)/poly(γ-glutamic acid) (γ-PGA) complexes. Ch is a biocompatible cationic polysaccharide extensively studied and γ-PGA is a biodegradable, hydrophilic and negatively charged poly-amino acid. These components interact electrostatically, due to opposite charges, resulting in self-assembled structures that can be designed to deliver active molecules such as drugs and proteins. Ch and γ-PGA were self-assembled into polyelectrolyte multilayer films (PEMs) of 371 nm thickness, using the layer-by-layer method. Interferon-γ (IFN-γ) was incorporated within the Ch layers at 100 and 500 ng/mL. Ch/γ-PGA PEMs with IFN-γ were able to modulate the phenotype of IL-10-treated macrophages at the cell cytoskeleton and cytokine profile levels, inducing an increase of IL-6 and a decrease of IL-10 production. More interestingly, the pro-invasive role of IL-10-treated macrophages was hindered, as their stimulation of gastric cancer cell invasion in vitro decreased from 4 to 2-fold, upon modulation by Ch/γ-PGA PEMs with IFN-γ. This is the first report proposing Ch/γ-PGA PEMs as a suitable strategy to incorporate and release bioactive IFN-γ with the aim of modulating macrophage phenotype, counteracting their stimulating role on gastric cancer cell invasion.